Potential Benefits of Antiviral African Medicinal Plants in the Management of Viral Infections: Systematic Review - Beressa, Tamirat Bekele; Deyno, Serawit; Mtewa, Andrew G.; Aidah, Namuli; Tuyiringire, Naasson; Lukubye, Ben; Weisheit, Anke; Tolo, Casim Umba; Ogwang, Patrick Engeu (Frontiers in Pharmacology, 2021)
Abstract Abstract Background: Viruses cause various human diseases, some of which become pandemic outbreaks. This study synthesized evidence on antiviral medicinal plants in Africa which could potentially be further studied for viral infections including Coronavirus disease 2019 (COVID-19) treatment. Methods: PUBMED, CINAHIL, Scopus, Google Scholar, and Google databases were searched through keywords; antiviral, plant, herb, and Africa were combined using ‘AND’ and ‘OR’. In-vitro studies, in-vivo studies, or clinical trials on botanical medicine used for the treatment of viruses in Africa were included. Results: Thirty-six studies were included in the evidence synthesis. Three hundred and twenty-eight plants were screened for antiviral activities of which 127 showed noteworthy activities against 25 viral species. These, were Poliovirus (42 plants), HSV (34 plants), Coxsackievirus (16 plants), Rhinovirus (14plants), Influenza (12 plants), Astrovirus (11 plants), SARS-CoV-2 (10 plants), HIV ( 10 plants), Echovirus ( 8 plants), Parvovirus (6 plants), Semiliki forest virus (5 plants), Measles virus (5 plants), Hepatitis virus (3 plants), Canine distemper virus (3 plants), Zika virus (2 plants), Vesicular stomatitis virus T2 (2 plants). Feline herpesvirus (FHV-1), Enterovirus, Dengue virus, Ebola virus, Chikungunya virus, Yellow fever virus, Respiratory syncytial virus, Rift Valley fever virus, Human cytomegalovirus each showed sensitivities to one plant. Conclusion: The current study provided a list of African medicinal plants which demonstrated antiviral activities and could potentially be candidates for COVID-19 treatment. However, all studies were preliminary and in vitro screening. Further in vivo studies are required for plant-based management of viral diseases. Keywords: SARS-CoV-2, Viral infections, African Medicinal Plants